2010
DOI: 10.2141/jpsa.010005
|View full text |Cite
|
Sign up to set email alerts
|

Production of Recombinant Chicken IgY-Fc and Evaluation of Its Transport Ability into Avian Egg Yolks

Abstract: Maternal immunoglobulin (Ig) Y, the avian counterpart of mammalian IgG, is e ciently transported into the yolks of maturing oocytes. We have previously shown that the Fc region plays a critical role in the IgY transport into avian egg yolks. The aim of this study was to produce recombinant IgY-Fc and to evaluate its transport ability into avian egg yolks. Two basic expression vectors were constructed: one mainly expressed three constant regions of chicken IgY heavy chain (Fc) that contained three cysteine resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…They mutated "C347" to the serine of IgY-Fcυ2-4, and this recombinant also retained high affinity binding to the chicken leukocyte IgY-Fc receptor, CHIIR-AB1. By introducing this methodology, we have succeeded in producing two recombinant chicken IgY-Fc(s) with different sizes, IgYFcυ2-4 (C347S) and IgY-Fcυ3-4 (C340S), retaining a high transport ability into the egg yolks of quail (Bae et al, 2010a). Interestingly, the transport ability of the IgY-Fcυ3-4 into the egg yolks corresponded closely with that of the IgY-Fcυ2-4, suggesting that the presence of Cυ3 and Cυ4 domains but not Cυ2 domain is important to maintain the transport ability of IgY.…”
Section: Studies Using Recombinant Ig and Site-directed Mutagenesis Tmentioning
confidence: 99%
See 1 more Smart Citation
“…They mutated "C347" to the serine of IgY-Fcυ2-4, and this recombinant also retained high affinity binding to the chicken leukocyte IgY-Fc receptor, CHIIR-AB1. By introducing this methodology, we have succeeded in producing two recombinant chicken IgY-Fc(s) with different sizes, IgYFcυ2-4 (C347S) and IgY-Fcυ3-4 (C340S), retaining a high transport ability into the egg yolks of quail (Bae et al, 2010a). Interestingly, the transport ability of the IgY-Fcυ3-4 into the egg yolks corresponded closely with that of the IgY-Fcυ2-4, suggesting that the presence of Cυ3 and Cυ4 domains but not Cυ2 domain is important to maintain the transport ability of IgY.…”
Section: Studies Using Recombinant Ig and Site-directed Mutagenesis Tmentioning
confidence: 99%
“…A recent study showed that ggFcR mainly interacts with the Cυ2 domain of IgY (Schreiner et al, 2012). However, the Cυ2 domain is not essential to maintain IgY-Fc transport capability into egg yolks (Bae et al, 2010a), suggesting that the likelihood of ggFcR involvement in IgY transport is low. A third receptor, CHIR-AB1, is a member of the leukocyte receptor family (Viertlboeck et al, 2005(Viertlboeck et al, , 2007.…”
Section: Relevance Of Igy-fc Receptor On Ig Uptake Into Egg Yolksmentioning
confidence: 99%
“…The heavy chains of IgY feature a variable region (VH) and four constant regions (CH1–CH4); in comparison, IgG features a variable region (VH) and three constant regions (CH1–CH3) (Figure 1). 17,19 Unlike IgG, IgY lacks a hinge region, which reduces swing and flexibility, thus resulting in increased stability 11 . The isoelectric point of IgY (5.7–7.6) is lower than that of IgG (6.1–8.5) 20 .…”
Section: The Molecular Characteristics Of Igymentioning
confidence: 99%
“…The heavy chains of constant regions (CH1-CH3) (Figure 1). 17,19 Unlike IgG, IgY lacks a hinge region, which reduces swing and flexibility, thus resulting in increased stability. 11 The isoelectric point of IgY (5.7-7.6) is lower than that of IgG (6.1-8.5).…”
Section: The Molecular Structure Of Igymentioning
confidence: 99%
“…First, Fc 3-4 was utilized for an uptake study, since the C 2 domain of Fc 2-4 is not essential for Fc uptake in chicken IgY (Bae et al, 2010a). Seven Fc 3-4 mutants were produced and were analyzed by SDS-PAGE (Fig.…”
Section: Uptakes Of Qigy-fc Mutants In Sequentially Laid Eggsmentioning
confidence: 99%